Prognostic value of canine frozen-thawed semen parameters on in vitro sperm-oocyte interactions - Silva, Alexandre R.; Cardoso, Rita de Cassia S.; Silva, Lucia D. M.; Chirinea, Viviane H.; Lopes, Maria Denise [UNESP]; Souza, Fabiana Ferreira de [UNESP] (Elsevier B.V., 2006)
Combining the data from conventional semen analysis with oocyte penetration assays should improve the assessment of the fertilizing ability of a semen sample. Thus, the objective of the present study was to evaluate the prognostic value of various semen parameters on the in vitro interactions between frozen-thawed canine sperm and homologous oocytes. Ten ejaculates from five stud dogs (two ejaculates/dog) were collected by digital manipulation. Semen samples were evaluated, extended in Tris-egg yolk-glycerol, frozen and stored in liquid nitrogen, and thawed several weeks later. Samples were evaluated for motility and sperm populations by computer-aided semen analysis (CASA), plasma membrane integrity (carboxy-fluorescein diacetate and propidium iodide), and sperm morphology (Bengal Rose). Thawed spermatozoa were also incubated with homologous oocytes for 18 h in an atmosphere of 5% CO2 and 95% air at 38 degrees C and sperm-oocyte interactions were evaluated. Simple linear regression models were calculated, with sperm parameters as independent variables and sperm-oocyte interactions as the dependent variable. There were significant associations between: percentage of oocytes bound to spermatozoa and beat cross frequency (BCF; R-2 = 63%); percentage of oocytes that interacted with spermatozoa and BCF (R-2 = 73%); and number of penetrated spermatozoa and velocity average pathway (VAP; R-2 = 64%) and velocity straight line (VSL; R-2 = 64%). Although plasma membrane integrity and sperm morphology had little prognostic value for in vitro interactions between canine frozen-thawed sperm and homologous oocytes, some motility patterns (evaluated by CASA) were predictive of in vitro sperm-oocyte interactions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: dog; semen; freezing; oocyte; CASA